Antimicrobial activity of cyanidin-3-O-glucoside–lauric acid ester against Staphylococcus aureus and Escherichia coli - Li Lili; Zhou Ping; Wang Yidi; Pan Ying; Chen Min; Tian Ye; Zhou Hua; Yang Baoru; Meng Hecheng; Zheng Jie (Elsevier, 2022)
Enzymatic acylation of anthocyanin with fatty acid improves its lipophilic solubility and application potential. Nevertheless, evaluation of functional properties of product is premise for application. This study investigated the antimicrobial potential and the underlying mechanisms of an acylated anthocyanin, namely, cyanidin-3-O-glucoside–lauric acid ester (C3G-LA), to provide guidelines for its application. C3G-LA exhibited outstanding antibacterial activity against Staphylococcus aureus [minimum inhibitory concentration (MIC) = 0.3125 mg/mL] and modest activity against Escherichia coli (MIC = 5 mg/mL). Moreover, C3G-LA manifested bactericide ability against S. aureus at 0.625 mg/mL. Decreases in membrane integrity (by 96% and 92% at MIC in S. aureus and E. coli, respectively), intracellular ATP concentration (by 96% and 92%) and intracellular pH (by 11% and 9%) and changes in cellular morphology altogether indicated the dysfunction of cell membrane under C3G-LA treatment. These findings demonstrated that C3G-LA could be adopted as an alternative food preservative against foodborne pathogens.